The evolutions achieved in companies with the implementation of Environmental, Social and Governance: Integrative review (International Journal of Business, Economics and Management, 2023)
Contemporary businesses are being actively prompted to craft innovative and environmentally responsible solutions. Integrating Environmental, Social, and Governance (ESG) practices can furnish companies with a plethora of competitive benefits, setting them apart in the market landscape. In line with this viewpoint, our current endeavor seeks to dissect how companies progress through the adoption of ESG measures, and the array of advantages this adoption brings forth. The study employed an integrative review methodology, which involves comprehensively examining and describing a topic by gathering information from various published sources. Through this research approach, it becomes evident that companies embracing ESG practices can realize cost savings linked to environmental, legal, and reputational risks. Moreover, such adoption leads to heightened operational efficiency and enhanced long-term resilience. Among the research findings, a clear trend has emerged where discussions surrounding the implementation of ESG within the business realm have grown significantly in recent years. In essence, this assertion emphasizes the significance of integrating ESG factors into investments. However, it's crucial to comprehensively grasp both their benefits and drawbacks. This, in turn, bolsters the organization's credibility, augments financial performance, and enhances overall productivity. This collective effort contributes to the cultivation of a more conscientious and responsible business ecosystem. The dedication to these principles should be authentic and tangibly manifested across all facets and undertakings of the company.